A feasible and acceptable multicultural psychosocial intervention targeting symptom management in the context of advanced breast cancer. Issue 2 (19th November 2019) - Teo, Irene; Vilardaga, Jennifer Plumb; Tan, Yee Pin; Winger, Joseph; Cheung, Yin Bun; Yang, Grace Meijuan; Finkelstein, Eric A.; Shelby, Rebecca A.; Kamal, Arif H.; Kimmick, Gretchen; Somers, Tamara J.
Abstract: Objective: Advanced breast cancer patients around the world experience high symptom burden (ie, distress, pain, and fatigue) and are in need of psychosocial interventions that target symptom management. This study examined the feasibility, acceptability, and engagement of a psychosocial intervention that uses cognitive‐behavioral strategies along with mindfulness and values‐based activity to enhance patients' ability to manage symptoms of advanced disease in a cross‐cultural setting (United States and Singapore). Pre‐treatment to post‐treatment outcomes for distress, pain, and fatigue were compared between intervention recipients and waitlisted controls. Methods: A pilot randomized controlled trial included women with advanced breast cancer (N = 85) that were recruited in the United States and Singapore. Participants either received the four session intervention or be put on waitlist. Descriptive statistics and effect size of symptom change were calculated. Results: The psychosocial intervention was found to be feasible as indicated through successful trial accrual, low study attrition (15% ), and high intervention adherence (77% completed all sessions). Acceptability (ie, program satisfaction and cultural sensitivity) and engagement to the study intervention (ie, practice of skills taught) were also high. Anxiety, depression, and fatigue scores remained stable or improved among intervention participants while the same symptoms worsened in the control group. In general, effect sizes are larger in the US sample compared with the Singapore sample. Conclusions: The cognitive‐behavioral, mindfulness, and values‐based intervention is feasible, acceptable, and engaging for advanced breast cancer patients in a cross‐cultural setting and has potential for efficacy. Further larger‐scaled study of intervention efficacy is warranted.